Invasive Pleomorphic-Type Lobular Carcinoma of the Breast Presenting as a Mucinous Carcinoma - A. Baig; G. Omeroglu-Altinel; A. Omeroglu (Case Reports in Pathology)
Invasive mucinous carcinoma of the breast is mostly associated with invasive carcinoma of no special type (NST) and sometimes with neuroendocrine type tumors such as solid papillary carcinoma. Extracellular mucin production in invasive lobular carcinoma (ILC) is extremely rare. To the best of our knowledge only 18 such cases have been described in the literature. Here we present a unique case of invasive pleomorphic-type lobular carcinoma (IPTLC) presenting as a mucinous carcinoma of the breast on core needle biopsy. Here we discuss the impact and ways to suspect such case.